Depression in parents of children with disability - Dimoski Sanja M. (Specijalna Edukacija i Rehabilitacija, 2020)
Introduction. Research shows that parental depression has negative effects on various spheres of children's psychophysical development. The subject of this paper is depression of parents of children with disability. Research on the presence of depression in parents of children with disabilitiy is presented, as well as research on differences in depression between fathers and mothers of children with disability, the relation between depression and the type of child's disability, and the relation of depression with demographic variables and parental support. Objective. This paper aims to analyze available research on the depression of parents of children with disability, the relation between depression and correlation variables, as well as to explain the research findings. The aim of the paper derives from the importance of the research subject for psychology of disability and rehabilitation. Methods. The method involved searching for scientific research available on relevant online search engines: Google Scholar, KoBSON, ScienceDirect. The basic search was performed on the basis of the following key words - depression and parents of children with disability. Results. The research analysis indicates the inconsistency of the results on the presence of depression in parents of children with disability. The paper provides findings that consistently suggest higher levels of depression in mothers compared to fathers of children with disability. Research practice indicates a link between depression and the type of disability, i.e. depression and behavioral characteristics of children with disability. There is no systematic research on the relation between parental depression in children with disabilities and demographic variables. The availability of professional support is negatively related to the presence of depression. Conclusion. The inconsistency of the results on the presence of depression in parents of children with disability is, to a large extent, a consequence of methodological reasons. Reducing depression in parents of children with disability has a double positive effect - on themselves and their children.